The application of saṅgahavatthu dhamma principles for increasing the social welfare’s service quality of tha pladuk subdistrict municipality in Mae tha district, lamphun province - Uttiya, Thanita (MCU Haripunchai Review, 2025)
This thesis aims to: 1) Study the quality level of social welfare service delivery. 2) Compare public opinions on the quality of social welfare service delivery, categorized by personal factors. and 3) Propose guidelines to enhance the quality of social welfare services. This is mixed-methods research. The quantitative part involved 382 residents aged 18 and over in the area of Tha Pladuk Subdistrict Municipality. The research instrument was a questionnaire with a reliability coefficient of 0.81. The data were analyzed using statistics such as frequency, percentage, mean, standard deviation, t-test, and F-test. The qualitative part included in-depth interviews with 14 key informants. The research revealed the following: 1)The overall public opinion on the quality of social welfare services in Tha Pladuk Subdistrict Municipality was at a high level. This included aspects such as staff friendliness, responsiveness to service users’ needs, respect and courtesy shown to service users, willingness to provide service, maintaining a positive organizational image, politeness and gentleness, and enthusiasm in service delivery. 2) When comparing public opinions on the quality of social welfare services, it was found that gender and average monthly income did not result in significant differences in opinions. However, age, educational background, and occupation did show significant differences, thereby supporting the research hypotheses. 3) The proposed guidelines for improving the quality of social welfare services in Tha Pladuk Subdistrict Municipality involved applying the four principles of Sangahavatthu (basis of social solidarity) as follows : 1) Dana (charity): Encourage volunteer spirit and enhance service delivery with willingness. 2) Piyavaca (kind speech): Improve the use of polite, gentle, and pleasant language toward service users. 3) Atthacariya (helpful conduct): Promote self-development plans that integrate knowledge with morality. 4) Samanattata (evenness): Foster a sense of responsibility and consistency in behavior and conduct.